2007
DOI: 10.1093/jxb/erm201
|View full text |Cite
|
Sign up to set email alerts
|

Transpiration efficiency of a tropical pioneer tree (Ficus insipida) in relation to soil fertility

Abstract: The response of whole-plant water-use efficiency, termed transpiration efficiency (TE), to variation in soil fertility was assessed in a tropical pioneer tree, Ficus insipida Willd. Measurements of stable isotope ratios (delta(13)C, delta(18)O, delta(15)N), elemental concentrations (C, N, P), plant growth, instantaneous leaf gas exchange, and whole-plant water use were used to analyse the mechanisms controlling TE. Plants were grown individually in 19 l pots with non-limiting soil moisture. Soil fertility was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
71
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 99 publications
(96 citation statements)
references
References 72 publications
22
71
3
Order By: Relevance
“…This extractable P concentration is in the high range of values typically observed for neotropical rainforest soils (Clinebell et al, 1995;Turner and Engelbrecht, 2011). We previously observed that the addition of rice husks to the soil mixture differentially reduced N availability relative to P availability, presumably due to microbial immobilization of available N (Cernusak et al, 2007b). Based on these considerations, the unfertilized soil treatments in our experiments likely had relatively low N availability compared with P availability.…”
Section: Plant Materials and Experimental Treatmentssupporting
confidence: 56%
See 1 more Smart Citation
“…This extractable P concentration is in the high range of values typically observed for neotropical rainforest soils (Clinebell et al, 1995;Turner and Engelbrecht, 2011). We previously observed that the addition of rice husks to the soil mixture differentially reduced N availability relative to P availability, presumably due to microbial immobilization of available N (Cernusak et al, 2007b). Based on these considerations, the unfertilized soil treatments in our experiments likely had relatively low N availability compared with P availability.…”
Section: Plant Materials and Experimental Treatmentssupporting
confidence: 56%
“…Thus, nodule formation can be suppressed by increasing the availability of N in the soil, as demonstrated for fertilized O. macrocalyx in this study, and by growth under low irradiance (McHargue, 1999). The unfertilized treatments in our experiments replicated a low-N gap environment, insofar as there was high irradiance (approximately 80% of full sunlight) and low soil N availability, caused by the addition of rice husks to the soil mixture (Cernusak et al, 2007b). Therefore, these experimental conditions should have led to maximal expression of nodule mass ratio and N 2 fixation, when compared with the range of conditions likely to be encountered by these species in their native environments.…”
mentioning
confidence: 92%
“…. The d was previously estimated to have a mean value of about 3‰ in 15 tropical tree species (Cernusak et al, 2008), with other estimates in the literature ranging from about 0 to 4‰ (Cernusak et al, 2007;Hubick, 1990;Hubick and Farquhar, 1989;Hubick et al, 1986). The c i /c a is controlled by the balance between photosynthesis (A) and stomatal conductance (g s ).…”
Section: Introductionmentioning
confidence: 99%
“…The 5 N ratio of plant leaves generally represents the (5 15 N ratio of the soil source the plant takes up, with nitrate having a lower (5 15 N ratio than ammonium in most cases (Hogberg 1997;but see Houlton 2007). Carbon isotope ratios have been used to represent integrated water-use efficiency over the leaf lifespan (Farquhar et al 1989;Baltzer et al 2005;Cernusak et al 2007). Leaf 5 C ratios arise from differences in the diffusivity of C and C in air and through the stomatal pathway, as well as from the enzymatic discrimination of the isotopes.…”
Section: Measurement Of Functional Traitsmentioning
confidence: 99%
“…Leaf 5 C ratios arise from differences in the diffusivity of C and C in air and through the stomatal pathway, as well as from the enzymatic discrimination of the isotopes. Plants that use water more efficiently exhibit less negative (5 13 C ratios (Farquhar et al 1989;Baltzer et al 2005;Cernusak et al 2007). Instantaneous water use efficiency (WUE) was calculated from A max ( area ) and transpiration according to Lambers et al (1998) where A max (area ) -area-based photosynthetic rate (umol CO2 m~ s~ ) and N area -area-based leaf N content (g N cm -2 ).…”
Section: Measurement Of Functional Traitsmentioning
confidence: 99%